THE COMPARATIVE ANALYSIS OF THE PERFORMANCE OF TRAFFIC FLOW USING MKJI METHOD, GREENSHIELDS MODEL, GREENBERG, AND UNDERWOOD ON THE WAY THE BASIS OF ULIN BANJARBARU KM.23 BANJARBARU (STA 23+450 - STA 23+650) - Jauhari Efendi; Rosehan Anwar (Universitas Lambung Mangkurat, 2019)
Traffic flow is one of the components that cannot be integral part with other components such as social activity, economic, cultural, population and land use patterns. Along with the growth of traffic flow increased rapidly, then there would be the density of traffic flow. This is because the density of the capacity of the motor vehicle on the street are very much, this can lead to delays.Three model approach through traffic Greenshields model, Greenberg, Underwood Manual and the capacity of the way Indonesia (MKJI) 1997 provide guidance to get the level of service of the road from a roads.The model equation for the flow of Banjarmasin to Banjarbaru namely model greenberg with equation y = -39,9ln(x)+179,7 and value of R of 0,7312 with maximum volume 1326,38 smp/hour, while for the current Banjarbaru to Banjarmasin obtained similarities with Greenberg Model, y = -14,32ln(x) + 102,23 and value of R of 6638,38 obtained when the volume of the maximum of 460 smp/hour.Based on the prediction that done, obtained the result that in the year 4 and year 5 the level of services in the way of Ahmad Yani Km.32 Banjarbaru located on the category of class E and F. So the need to be done so that the level of services can be increased and become better.Key Words: Greenshields, Greenberg, Underwood, MKJI, prediction.